2014
DOI: 10.1007/s12011-014-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

A Mineral and Antioxidant-Rich Extract from the Red Marine Algae Alsidium corallinum Exhibits Cytoprotective Effects Against Potassium Bromate-Induced Erythrocyte Oxidative Damages in Mice

Abstract: The present study was carried out to investigate potassium bromate toxicity in mice and the corrective effects of marine algae Alsidium corallinum. The red algae demonstrated its rich composition in phenols, triterpenes, flavonoids, alkaloids, tropolones, sodium, potassium, calcium, magnesium, iron, copper, and zinc. To confirm its antioxidant potential, an in vivo study was performed on adult mice. The animals were divided into four groups: group I were used as controls, group II received potassium bromate (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The effects of KBrO 3 treatment are likely due to increased lipid peroxidation and the generation of its reactive metabolites, including ROS. Therefore, the amelioration induced upon A. corallinum supplementation could be due to its large antioxidant phenolic content (Ben Saad et al, ). Thus, treatment with A. corallinum restored normal glomerular filtration and renal function, and normalized these markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of KBrO 3 treatment are likely due to increased lipid peroxidation and the generation of its reactive metabolites, including ROS. Therefore, the amelioration induced upon A. corallinum supplementation could be due to its large antioxidant phenolic content (Ben Saad et al, ). Thus, treatment with A. corallinum restored normal glomerular filtration and renal function, and normalized these markers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the alga Alsidium corallinum , a Rhodophyta of the order Ceramiales with a wide distribution along all Mediterranean coasts, as well as the Atlantic islands of Madeira and the Canaries (Guiry and Guiry, ). Recently, we found that an ethanolic extract of A. corallinum exhibits high levels in secondary compounds such as phenolic acids, flavonoids, anthocyanins, chlorophyll, carotenoids, alkaloids, triterpenes, and tropolones, conferring a strong antioxidant activity to that extract (Ben Saad et al, ). Moreover, the alga is rich in minerals (sodium, potassium, calcium, magnesium, iron, copper, and zinc) (Ben Saad et al, ) and its ethanolic extract showed strong inhibition of bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocytes are one of the many cell types in which a redox imbalance can occur. Fatty acids in the membranes, elevated oxygen levels, and the presence of hemoglobin inside make erythrocytes a natural target for free radicals [ 7 ]. The oxidative processes in the erythrocytes entail membrane injury, modifications of the membrane's structural and functional elements, and changes in the membrane architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative processes in the erythrocytes entail membrane injury, modifications of the membrane's structural and functional elements, and changes in the membrane architecture. All these processes cause an increase in erythrocytes' mean osmotic fragility and inhibition of Mg 2+ and Ca 2+ ATPase activity [ 7 ]. The survival of erythrocytes in the circulating blood plasma depends on the structural and functional integrity of their membranes, which determines the mechanical behavior of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation